(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The aim of the present study is to focus on the Land-ownership and Tenancy with their agrarian relations of the Haryana province from 1800 to 1947 and includes the districts of Hisar, Ambala, Karnal, Rohtak and Gurgaon. Primary data has been taken for achieving eg the objective of the study. The bilingual state of Haryana was bifurcated and consequentially this south-eastern area was declared a separate state on 1st, November 1966, known as Haryana.